2003
DOI: 10.1097/00001888-200305000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Access to Medical Education for Students from Medically Underserved Communities

Abstract: The Premedical Honors College (PHC) is an eight-year, BS-MD program created in 1994 by Baylor College of Medicine (BCM) and The University of Texas-Pan American (UT-PA) to increase the number of physicians addressing the health care needs of underserved populations in Texas. The PHC targets South Texas, a 13-county, medically underserved area with a population that is 82% Hispanic. To date, the PHC has had 159 matriculants and 71 graduates, of whom 60 (84.5%) have matriculated into medical school. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 2 publications
1
39
0
Order By: Relevance
“…Examples of such programs include the Premedical Honors College, an eight-year high-school-through-medical-school program created by Baylor College of Medicine and The University of Texas-Pan American, and the intensive Summer Medical and Dental Education Program (SMDEP) that prepares undergraduate students in science, writing, and test-taking skills. 5,21 The long-term impact of these programs on faculty diversity should be evaluated, since our results suggest that investment in this type of program may be one of the most effective strategies in improving faculty diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such programs include the Premedical Honors College, an eight-year high-school-through-medical-school program created by Baylor College of Medicine and The University of Texas-Pan American, and the intensive Summer Medical and Dental Education Program (SMDEP) that prepares undergraduate students in science, writing, and test-taking skills. 5,21 The long-term impact of these programs on faculty diversity should be evaluated, since our results suggest that investment in this type of program may be one of the most effective strategies in improving faculty diversity.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the lack of or shortage of educational materials, services, or access that in many cases are available to middle and upper class families — books in the home, access to quality pre-K programs, a parent who can serve as a role model and guide for their child’s educational advancement, and well-resourced schools and after-school and summer programs — all of which profoundly contribute to success at every point along the academic pipeline (K-16) [25,26,27]. …”
Section: Methodsmentioning
confidence: 99%
“…Without it, it is difficult to convince minority students or faculty that they are valued and supported. Beyond the admissions process there must be greater investment in student support services, such as mentoring, tutoring, student wellness, and “an early warning system” to identify and help students in academic distress [27]. …”
Section: Methodsmentioning
confidence: 99%
“…A well-designed evaluation found that the number of UT-PA graduates matriculating into medical school dramatically increased after implementation of the honors program, demonstrating that a comprehensive college-level program can boost the overall number of minority students from an underserved region entering medical school. 14 …”
Section: Why Minorities Are Underrepresented In the Health Professionmentioning
confidence: 99%